Chinese Medicinal Herb-Derived Carbon Dots for Common Diseases: Efficacies and Potential Mechanisms - Li, Dan; Xu, Kun-yan; Zhao, Wei-peng; Liu, Ming-feng; Feng, Rui; Li, De-qiang; Bai, Jing; Du, Wen-li (Frontiers in Pharmacology, 2022)
The management of hemorrhagic diseases and other commonly refractory diseases (including gout, inflammatory diseases, cancer, pain of various forms and causes) are very challenging in clinical practice. Charcoal medicine is a frequently used complementary and alternative drug therapy for hemorrhagic diseases. However, studies (other than those assessing effects on hemostasis) on charcoal-processed medicines are limited. Carbon dots (CDs) are quasi-spherical nanoparticles that are biocompatible and have high stability, low toxicity, unique optical properties. Currently, there are various studies carried out to evaluate their efficacy and safety. The exploration of using traditional Chinese medicine (TCM) -based CDs for the treatment of common diseases has received great attention. This review summarizes the literatures on medicinal herbs-derived CDs for the treatment of the difficult-to-treat diseases, and explored the possible mechanisms involved in the process of treatment.